Telehealth: "virtual" lifeline for home-ventilated patients during the COVID-19 pandemic. Issue 3 (28th September 2020) - Soo, Chun Ian; Chan, Yeow; Loh, Ee Chin; Pang, Yong Kek
The evolution of positive airway pressure (PAP) devices since their introduction by Colin Sullivan in 1980 has witnessed growing evidence supporting their use for medical conditions associated with chronic ventilatory failure. The emergence of PAP devices also resulted in a higher number of patients requiring long-term medical care and ventilation. The concept of "hospital at home" with home ventilation to ease the burden on overwhelmed hospitals was evident when the prevalence of home mechanical ventilation (HMV) users reported in 2016 was at 10.9 per 100 000 population [1]. Telehealth appears useful to fill in the void for home-ventilated patients to maintain the much-needed connectivity with their healthcare team during the #COVID19 pandemic https://bit.ly/3ftvjxW